2022
DOI: 10.4018/978-1-7998-8921-2.ch013
|View full text |Cite
|
Sign up to set email alerts
|

Effective Teaching Strategies for Chinese International Students at a Canadian University

Abstract: Challenges that Chinese international students with low academic English proficiency encounter in academic reading and writing were exacerbated by remote learning during the COVID-19 pandemic. Qualitative and quantitative data were collected and analyzed from an online reading-writing support program at a Canadian university to examine Chinese students' challenges, perceptions of learning, as well as the impact of culturally responsive pedagogy (CRP) used in the program. The study indicates the benefits of CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…An analysis of this approach from the perspective of academic integrity socialization (Khoo and Kang, 2022) showed that opportunities to develop personal connections with academic integrity practice contributed to learners voluntarily writing more than 6,000 words within a month in their co-curricular writing support program. When culturally responsive pedagogy (Gay, 2018) was integrated with the LeD-InF approach, Huo and Khoo (2022) reported that of the 14 low-proficiency learners in their study, eight wrote on average 11,454 words and three wrote on average 6,437 words in one month. Since participation in the co-curricular program was voluntary, the authors interpreted this high volume of written output as an indication of learners' engagement with the program and its usefulness to them.…”
Section: Need For Inclusive Learning Opportunitiesmentioning
confidence: 99%
“…An analysis of this approach from the perspective of academic integrity socialization (Khoo and Kang, 2022) showed that opportunities to develop personal connections with academic integrity practice contributed to learners voluntarily writing more than 6,000 words within a month in their co-curricular writing support program. When culturally responsive pedagogy (Gay, 2018) was integrated with the LeD-InF approach, Huo and Khoo (2022) reported that of the 14 low-proficiency learners in their study, eight wrote on average 11,454 words and three wrote on average 6,437 words in one month. Since participation in the co-curricular program was voluntary, the authors interpreted this high volume of written output as an indication of learners' engagement with the program and its usefulness to them.…”
Section: Need For Inclusive Learning Opportunitiesmentioning
confidence: 99%